Markion und der biblische Kanon - Cameron, Averil (Hans-Lietzmann-Vorlesungen, 2016)
This public lecture is staged annually in memory of the ecclesiastic historian Hans Lietzmann (1875-1942), Adolf von Harnacks's successor as director of the Academy project The Greek Christian Authors of the First Centuries (GDS). The invited speaker is an internationally renowned scholar from the field of classical studies. The lectures address central topics of the history of ancient religion that are of relevance to the present day.